2017
DOI: 10.1039/c7mb00381a
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic alterations of in vitro macrophage infection by L. infantum and L. amazonensis

Abstract: Particular lipid profiles have been found in two different protozoa of the Leishmania genus. Leishmania infantum, a visceral leishmaniasis causative agent and Leishmania amazonensis, a cutaneous leishmaniasis, reveal distinctive lipid contents of phosphatidylethanolamine and phosphatidylserine plasmalogens, sphingolipids, phosphatidylinositols, phosphatidylcholine, and phosphatidylethanolamine, which have been shown to be related to species, life-cycle of the parasite, and macrophage infection. L. infantum dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…PCs were also increased in the infected footpad ( Table 3 and Table 4 , Figure 3 ). This increase concurs with prior reports of elevated lysophosphatidylcholine (LPC) and PCs in infected macrophages in vitro [ 23 , 28 ]. Concordance between infection models supports our approach and translatability of results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PCs were also increased in the infected footpad ( Table 3 and Table 4 , Figure 3 ). This increase concurs with prior reports of elevated lysophosphatidylcholine (LPC) and PCs in infected macrophages in vitro [ 23 , 28 ]. Concordance between infection models supports our approach and translatability of results.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, changes in the host plasma metabolite abundance, including pyruvate, taurine and N -acetylglutamine, can serve as an indicator of response to CL treatment [ 19 ]. Several studies previously investigated Leishmania and host metabolism during in vitro macrophage infection [ 20 , 21 , 22 , 23 ], or in amastigotes purified from mouse granulomatous lesions [ 24 ], but there is still a lack of knowledge of host metabolic responses during in vivo infection.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the bands in the spectral region around 1350 cm -1 , which is obvious in many of the vacuole spectra, are assigned to different protein and sugar components, as well as to inositol [235], likely reflecting the presence of modified lipids and proteins. In Leishmania, glycoinositol-phospholipids have been shown to be an abundant molecular class [255,256], in addition to lipids that have an additional ether double bond at the sn-1 position [257]. In addition to the high abundance of lipids and glycosylated lipids, distinct vibrational modes of cholesterol as discussed above, and also of ergosterol are observed.…”
Section: Sers Spectra From Leishmania Infected Cellsmentioning
confidence: 94%
“…Recent transcriptomics, lipidomics, , and proteomics studies have demonstrated how different species of Leishmania modulate the host in order to survive and proliferate . Our most recent studies , compared an inflammation model to different species of Leishmania spp.…”
mentioning
confidence: 99%